Acute urinary retention in children - Agarwal, Brijesh Kumar; Agarwal, Namita (International Surgery Journal, 2017)
Background: Acute urinary retention is relatively infrequent in children. There are a variety of causes that are poorly defined in the literature and they differ from those seen in adult. Methods: We review our experience with pediatric patients presenting with urinary retention at Sri Ram Murti Smarak- Institute of Medical Sciences, Bareilly. Children were reviewed from January 2012 to December 2015 from the record section of our institution. We selected 38 children for this study, of which 24 were boys and 14 girls. Results: The most common cause in our study was mechanical obstruction in 18 children (47%). Infections were documented in 8 children (20%). Neurological causes were identified on X-rays and urodynamic studies in 5 children (13%). We could not find any cause in 3 (9%) cases (idiopathic or behavorial). 2 (5.5%) children had fecal impaction as a cause. 2 (5.5%) girls had a Gynaecological cause. 20 patients out of 38 underwent surgical procedures. 5 children under went clean intermittent catheterization programme. 13 patients were kept on medical treatment. Our study is similar to previous studies in terms of aetiology but quite different in incidence of different aetiologies. This difference in incidence might be due to different population studied in various studies. Conclusions: Urinary retention in children is relatively rare. Urinary retention in children has various etiologies. Timely diagnosis and prompt treatment is needed because it is often associated with severe underlying disorders.